High Gain and Broadband Quasi Horn Antenna Array for Ku Band Mobile TV Antenna Systems and Monopulse Radiation - Tulum, Mehmet Akif; Turk, Ahmet Serdar (IEEE, 2019)
In this paper, a quasi-horn antenna array, which is combination of 16 x 4 slot array and its flares, is separately designed for Ku band mobile TV antenna systems and monopulse radiation. The slots are fed by waveguide power divider. For mobile TV antenna, this antenna is designed and fabricated with only TE10 sum port. In order to obtain sum and difference radiation pattern, a magic T is utilized and designed end of the waveguide feeder for monopulse radiation. Slot dimensions and distance between each slot are adjusted and optimized to get high gain and low return loss using 3D EM simulation. Short depth flares are added to aperture of each 4 x 1 slots to enhance gain of the array. According to the simulation results, gain of the array at the only sum port is 27.9 dBi @12 GHz dBi and 2 GHz bandwidth for mobile TV Antenna. For monopulse radiation, gain of the array at the sum port on magic T is 27.8 dBi @12 GHz and 1.5 GHz bandwidth. At the difference port, monopulse radiation pattern have 24.2 dBi maximum gain and -64 dB null. Return losses at the sum and difference port are lower than -6 dB in the operation band. Total dimensions of the 16 x 4 array prototype for mobile TV antenna are 34 cm x 9.5 cm x 5.5 cm and weight is 3.6 kg.
Keywords: quasi horn; dielectric load; slot array; ku band; mobile tv antenna; monopulse; MICROSTRIP ANTENNA; PERFORMANCE; Engineering; Physics